Investigation of the short-circuit current increase for PV modules using halved silicon wafer solar cells - Guo, Siyu; Schneider, Jens; Lu, Fei; Hanifi, Hamed; Turek, Marko; Dyrba, Marcel; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2015)
It is well established that using halved silicon wafer solar cells in a photovoltaic (PV) module is an efficient way to reduce cell-to-module resistive losses. In this work we have shown that PV modules using halved cells additionally show an improvement in their optical performance, resulting in a higher current generation. We attribute this increase in current to gains in light reflected from the backsheet area. An optical model is presented that quantitatively determines the influence of the backsheet on the short-circuit current of a PV module. We find that, for an accurate prediction, several factors have to be taken into account, including the geometry of the module, the backscattering properties of the backsheet and the illumination spectrum. Particularly the angularly and spectrally resolved scattering properties of the backsheet are shown to have a large impact on the current generation. Furthermore, light beam induced current (LBIC) measurements are used to test the backscattering properties of the backsheet and also the influence of the illumination spectrum. LBIC measurements are also used to verify the simulation results, giving good agreement. Thus the design of a PV module can be optimized by simulation. A standard full-size cell module and a halved-cell module with optimized cell spacing are fabricated. Compared to the standard module, the half-cell module is shown to have 4.60% more power (315.3 vs. 329.8 W), 1.46% higher fill factor (75.5 vs. 76.6%), and 3.08% more current (9.08 vs. 9.36 A).
CRIS-Team Scopus Importer:2023-03-07
Keywords: Crystalline silicon; Halved cells; PV module; Short circuit current; Silicon wafer solar cells